P36 Distribution of physical activity amenities in Scotland by small area measures of deprivation and urbanicity. (16th November 2010) - Lamb, K E; Ellaway, A; Ferguson, N S; Wang, Y; Ogilvie, D
Abstract : Objective: Obesity and physical activity are associated with aspects of the physical environment where people live, but the precise mechanisms of these associations are not well understood. Knowledge of the extent to which access to opportunities for physical activity is socially patterned is important to inform policy. A few studies of cities and regions (mostly conducted outside the UK) have found fewer resources in deprived areas, while others have not. The aim of this study was to examine the distribution of physical activity facilities by area level deprivation in Scotland, adjusting for differences in urbanicity and population density and specifically examining differences between Scotland's four largest cities. Design: A SportScotland data set, containing information about all Scottish sports facilities (n=10 283), was linked to Scottish Neighbourhood Statistics data on population size, deprivation category and urban classification for Scottish data zones. Poisson and negative binomial multilevel models were used to examine the association between facilities and deprivation quintiles, adjusting for random variation between local authorities. Setting: Scotland. Results: Prior to adjustment for urbanicity, the density of all facilities fell with increasing deprivation from quintiles 2 to 5. After adjustment for urbanicity and local authority, the effect of deprivation remained significant but the pattern altered, with data zones in quintile 3 having the highest estimated mean density of facilities (2.63/1000 residents). The lowest estimated densities were observed in the most affluent (1.99/1000) and the most deprived (1.87/1000) quintiles, with no significant difference between these quintiles. After adjusting for population size, Dundee and Edinburgh had the highest estimated density of facilities whilst Glasgow had the lowest. Conclusions: Facility presence is dependent upon area level deprivation, after taking into account differences between local authorities and urban classification, with both the least and most deprived areas showing the lowest rates of facilities. The distribution of facilities across Scotland does appear to be socially patterned, but not according to a straightforward social gradient. There is a need to go further and take transport accessibility into account.